Solid Electrolytes: A New Lithium‐Ion Conductor LiTaSiO5: Theoretical Prediction, Materials Synthesis, and Ionic Conductivity (Adv. Funct. Mater. 37/2019). (10th September 2019) - Wang, Qi; Wu, Jian‐Fang; Lu, Ziheng; Ciucci, Francesco; Pang, Wei Kong; Guo, Xin
Abstract : In article number1904232, Francesco Ciucci, Wei Kong Pang, Xin Guo, and co‐workers design and synthesize a novel lithium‐ion conductor LiTaSiO5, in which additional lithium ions are introduced into lattice sites of high energy through Zr‐doping, thereby favoring the concerted motion of lithium ions and lowering the energy barrier for the ion transport. This work demonstrates the power of theory in designing new materials.